2018
DOI: 10.1038/s41467-018-04941-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of Tousled-Like Kinase 2 activation

Abstract: Tousled-like kinases (TLKs) are required for genome stability and normal development in numerous organisms and have been implicated in breast cancer and intellectual disability. In humans, the similar TLK1 and TLK2 interact with each other and TLK activity enhances ASF1 histone binding and is inhibited by the DNA damage response, although the molecular mechanisms of TLK regulation remain unclear. Here we describe the crystal structure of the TLK2 kinase domain. We show that the coiled-coil domains mediate dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 74 publications
(103 reference statements)
9
56
0
1
Order By: Relevance
“…A model of the TLK1B kinase domain was constructed by homology modeling using the ROBETTA de novo protein structure prediction server ( Song et al., 2013 ) (see Transparent Methods in Supplemental Information ) and further compared/aligned to the published crystal structure of the highly homologous TLK2 ( Mortuza et al., 2018 ). A PDB file for the structure was included as Data S1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A model of the TLK1B kinase domain was constructed by homology modeling using the ROBETTA de novo protein structure prediction server ( Song et al., 2013 ) (see Transparent Methods in Supplemental Information ) and further compared/aligned to the published crystal structure of the highly homologous TLK2 ( Mortuza et al., 2018 ). A PDB file for the structure was included as Data S1 .…”
Section: Resultsmentioning
confidence: 99%
“…To confirm these results and the specificity of the TLK1 inhibition with a genetic approach that could obviate potential off-target effects of J54, one possibility would be to deplete TLK1, but this is problematic because of the redundant function of TLK2. However, an alternative is to overexpress a dominant kinase-dead TLK1 (TLK1-KD) because this protein can inhibit both TLK1 and TLK2 as these kinases homo- and hetero-dimerize for full activation ( Mortuza et al., 2018 ). In fact, we have reported that overexpression of TLK1-KD efficiently suppresses pNek1-T141 ( Singh et al., 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…In order to comprehensively map phosphorylation sites and to determine their stoichiometry in a purified protein by LC-MS/MS, it is essential to obtain its full sequence coverage 57 The mass spectrometric analysis of the ProAlanase digestion mixture resulted in 90% sequence coverage of the N3CID protein, while tryptic peptides covered 85% of the sequence (Fig. 5, a).…”
Section: Proline-rich Proteinmentioning
confidence: 99%
“…Our variant is located at the N-terminus in a region where no functional domains are known ( Figure 3 ). This region however is expected to contain a nuclear localization signal (NLS) as mutants lacking the first 160 amino acids fail to localise to the nucleus ( 6 ). In addition, more than 20 phosphorylation sites, including p.Thr52 and p.Tyr70, have been identified in the N-terminal domain of TLK2, suggesting that this is potentially an important regulatory domain in vivo ( https://www.phosphosite.org ).…”
Section: Discussionmentioning
confidence: 99%